The missionary's farewell: valedictory services of the Rev. John Williams, previous to his departure for the South seas; with his parting dedicatory address, to the British churches and the friends of missions - Campbell, John (D. Appleton, 1838)
Introductory prayer, by J.P. Smith.--Opening address, by W. Bateman.--Origin, progess, and future prospects of the South Sea mission, by W. Ellis.--Christian friendship, and considerations which mitigage the sorrows of separation, by J. Clayton.--Success of Mr. Williams's labours; his position as a missionary: and presentation of books, by J. Campbell.--Missionary objects, means, motives, and encouragements, by J. Williams.--Commendatory prayer, by G. Clayton.--Narrative of the excursion to the missionary ship and subsequent events, by J. Campbell.--Report of the Committee of the Common Council of the city of London, on the petition of the Rev. John Williams.